2020
DOI: 10.2147/jhc.s277870
|View full text |Cite
|
Sign up to set email alerts
|

<p>Gut Microbiota, Peroxisome Proliferator-Activated Receptors, and Hepatocellular Carcinoma</p>

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors in the world. HCC incidence rate is sixth and mortality is fourth worldwide. However, HCC pathogenesis and molecular mechanisms remain unclear. The incidence of HCC is associated with genetic, environmental, and metabolic factors. The role of gut microbiota in the pathogenesis of HCC has attracted researchers’ attention because of anatomical and functional interactions between liver and intestine. Studies have demonstrated the involvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 180 publications
(154 reference statements)
0
29
0
Order By: Relevance
“…PPARs, nuclear hormone receptors, could be activated by fatty acids and their derivatives and PPAR agonists are beneficial for the treatment of non-alcoholic fatty liver disease (NAFLD), liver fibrosis, and HCC ( Cao et al, 2009 ). Recent, studies demonstrated that PPARs participate in the progression of gut microbiota inhabitation and adaptation which is related to the pathogenesis of HCC ( Yu et al, 2020 ). These signaling pathways were shown to be associated with HCC progression in our analysis and were consistent with those reported in published literature.…”
Section: Discussionmentioning
confidence: 99%
“…PPARs, nuclear hormone receptors, could be activated by fatty acids and their derivatives and PPAR agonists are beneficial for the treatment of non-alcoholic fatty liver disease (NAFLD), liver fibrosis, and HCC ( Cao et al, 2009 ). Recent, studies demonstrated that PPARs participate in the progression of gut microbiota inhabitation and adaptation which is related to the pathogenesis of HCC ( Yu et al, 2020 ). These signaling pathways were shown to be associated with HCC progression in our analysis and were consistent with those reported in published literature.…”
Section: Discussionmentioning
confidence: 99%
“…AVT with potent oral nucleos(t)ide analogs (NUCs), such as entecavir or tenofovir disoproxil fumarate, can lead to virological and biochemical remission and prevent disease progression to hepatocellular carcinoma (HCC) and/or liver cirrhosis (1–4). HBV induces carcinogenesis via multiple pathways, and it is difficult to eradicate the risk of HCC, which remains a major issue from the perspective of public health and socioeconomic burden (5–11). Therefore, along with effective AVT, periodic surveillance is required to detect early-stage HCC and allow timely interventions with a curative intent (2,12–14).…”
Section: Introductionmentioning
confidence: 99%
“…The pathways involving the peroxisome proliferator-activated receptors (PPARs) could have a role in the HCC development. Published data reported their protective role in chronic liver disease development through an interplay with the microbiome and their ability to reverse leaky gut conditions and dysbiosis[ 65 ].…”
Section: Cancer Developmentmentioning
confidence: 99%
“…Although specific studies on cancer progression are lacking, targeting the PPARs could represent, at least, a cancer prevention strategy. Further details can be found elsewhere[ 65 ].…”
Section: Future Perspectives: Options For Cancer Preventionmentioning
confidence: 99%